Kontribusi Kualitas Layanan terhadap Kepuasan Serta Dampaknya pada Loyalitas Pelanggan - Cecep Hidayat; Putri Melinda (The Winners, 2009)
The purpose of this research is to find contribution of service quality towards building customer satisfaction, and the contribution of service quality towards customer loyalty, and the contribution of both service quality and customer satisfaction towards customer loyalty simultaneously, and find out whether there is any contribution of customer satisfaction to customer loyalty. The type of research used is associative survey and the analysis technique used is path analysis. The data are obtained through a survey with questionaire as the main instrument. This questionnaire is distributed to customers of Indosat  BlackBerry ISATBB community. Results showed that there are positive and significant contributions of service quality towards customer satisfaction, customer satisfaction to customer loyalty, and service quality to customer loyalty all directly or indirectly.